Drinking no more arsenic: Switching water source through intensive awareness programme in rural Bangladesh - Hossain, Zabed; Gani, Md. Showkat; Jakariya, Md.; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
The study assessed the effects of intensive awareness raising activities implemented from June 1999 to December 2001 among the arsenic exposed people to motivate towards safe water use. A total of 839 families those who used to drink arsenic contaminated water prior to intervention was selected randomly for the survey. Data revealed that 47.6% of the people switched from unsafe to safe water sources. Awareness on alternative safe water options played great role in motivating people towards safe water use. Rate of switching over was almost three times higher among the people those who were aware of alternative water options than those who were not. People with better education, high occupation and socio economic status showed the maximum rate of switching over towards safe water sources. People having the capacity to buy water options were seven times in number in changing their water source compared to those who have no capacity to buy. Integrated approach should be taken immediately to increase awareness on alternative water options, socio-economic status to increase their capacity to purchase water options.